Developing Muslim Self-Identity Through Contemporary American Literature - Mohd Nazri, Latiff Azmi (2013)
Teaching literature for second language learners would be a challenging job due to language barrier and misinterpretation of ideas especially when the text is not in the same culture, belief and understanding shared between the author and reader. This paper is a study on a content analysis of a contemporary American literature written by an avid postmodernist who has received a well-known acknowledgement by American poets and critics. The researcher chose Sarah Groham’s Bad Daughter to investigate the link between contemporary American literature and Islamic views, to analyze the text using the concept of postmodernism and most importantly to prove that all literary texts can be analyzed in educational approach as long as the analysis will not jeopardize the learner’s understanding towards his religion. This approach is parallel with the concept of postmodernism in literatur